Comprehensive Geriatric Assessment (Practical Issues in Geriatrics,, 2018)
This book offers an up-to-date review on the principles and practice of multidimensional assessment and management of the older individual, which represents the cornerstone of modern clinical practice in the elderly. The early chapters cover the main elements and scope of the comprehensive geriatric approach and explain the pathways of care from screening and case finding through to in-depth assessment and treatment planning. Subsequent chapters review the evidence of how best to apply the multidimensional assessment and management approach in defined healthcare settings and within specific clinical areas, such as cancer and surgery. Finally, the education and training challenges are reviewed and the prospects for future clinical service and research in this important field are examined. The book is very timely given the recent advances in application of this approach, which reflect the growing international realization that older people are "core business" in many clinical areas where the role of specialist geriatric medicine has hitherto been limited. Accordingly, the book will be relevant to a wide range of clinicians. The authorship comprises many of the best known and widely published experts in their respective fields.